Feeding Practices among Infants in a Rural Community in Bangladesh: A Cross-Sectional Study - Rajat Das Gupta (University Library System, University of Pittsburgh, 2015)
Background: Proper feeding practices during infancy are necessary for the growth and development of infants and to prevent malnutrition. This study was conducted to describe the feeding practice among infants in a rural area in Bangladesh. Methods: A cross-sectional study was conducted between February and June 2013. Data was collected through face-to-face interviews of 212 mothers using a pretested questionnaire. Results: Exclusive breast feeding and complementary feeding rates were 40.6% and 97.3%, respectively. One third of the mothers practiced prelactal feeding, and honey was the most common item. Maternal illness (72.7%) was the most common reason for not giving breast milk. Infant formula was used as an alternative food in majority of the cases (72.7%). Conclusion: Percentage of exclusive breast feeding was not satisfactory. Encouragement of female education is recommended to improve feeding practices and infant care.